Pengaruh Modul Pembelajaran Berbasis Problem Based Learning terhadap Hasil Belajar - Sulistiyani Sulistiyani (Universitas Indraprasta PGRI Jakarta, 2017)
The purpose of this study is to analyze (1) the validity and (2) the effectiveness of a problem-based learning module of economics for class XI IPS in second semester. It is a research on the effect of the use of problem-based learning module of economics for class XI in second semester on the improvement of the students? reliable learning results in Economics. The population of this research is 165 students of Class XI of SMA Negeri 1, Bandar Sribhawono, Lampung Timur, in Academic Year 2014/2015. The research samples consisting of 60 students: 30 in control class and 30 in experimental class are taken using a purposive sampling technique. The problem-based learning module of economics for class XI in second semester is effective in improving students? learning results, as indicated by the average score of the learning result of the control class and the experimental class, namely: 78.57 and 83.47 respectively. This indicates that the learning result of the experimental class are more excellent than that of the class control. The significance value of 2-tailed t test is 0.003, which is less than 0.050, meaning that the proposed H1 is rejected. It shows that there is a difference in students? average learning results between the students of the control class and those of the experimental class. In conclusion, the improvement of the learning result of the experimental class is better than that of the control class.